Influence of trabecular bone quality and implantation direction on press‐fit mechanics. Issue 2 (18th April 2016) - Damm, Niklas B.; Morlock, Michael M.; Bishop, Nicholas E.
ABSTRACT: Achieving primary stability of uncemented press‐fit prostheses in patients with poor quality bone can involve axial implantation forces large enough to cause bone fracture. Radial implantation eliminates intraoperative impaction forces and could prevent this damage. Platens of two commercial implant surfaces ("Beaded" and "Flaked") were implanted onto trabecular bone specimens of varying quality in a press‐fit simulator. Samples were implanted with varying interference, either axially (shear) or radially (normal). Push‐in and pull‐out forces were measured to assess stability. Microstructural changes in the bone were determined from μCT analysis. For force‐defined implantation analysis, push‐in and pull‐out forces both increased proportionally with increasing radial force, independent of implantation direction, bone quality or implant surface. For position‐defined implantation analysis, pull‐out forces were generally found to increase with interference and to be greater for radial than axial implantation direction, and to be lower for poor quality bone. Bone density increased locally at the tested interface due to implantation, in particular for the Beaded surface under axial implantation. If a safe radial stress can be determined for cortical bone in a particular patient, the associated implantation force, and pull‐out force which represents primary stability, can be directly derived, regardless of implantation direction, bone quality or implant surface. Radial implantation delivers primary stability that is no worse than that for axial implantation and may eliminate potentially damaging impaction forces. Development of implant designs based on this principal might improve implant fixation. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:224–233, 2017.